2003
DOI: 10.1210/jc.2002-021940
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ghrelin on the Insulin and Glycemic Responses to Glucose, Arginine, or Free Fatty Acids Load in Humans

Abstract: Ghrelin possesses central and peripheral endocrine actions including influence on the endocrine pancreatic function. To clarify this latter ghrelin action, in seven normal young subjects [age (mean +/- SEM), 28.3 +/- 3.1 yr; body mass index, 21.9 +/- 0.9 kg/m(2)), we studied insulin and glucose levels after acute ghrelin administration (1.0 microg/kg i.v.) alone or combined with glucose [oral glucose tolerance test (OGTT), 100 g orally], arginine (ARG, 0.5 g/kg i.v.) or free fatty acid (FFA, Intralipid 10%, 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 59 publications
(64 reference statements)
4
68
0
6
Order By: Relevance
“…On the basis of a C-terminal Gly-Lys motif, amidation of obestatin was assumed and verified as a prerequisite for biological activity [162]. Furthermore, the mass spectrometric data indicated that this peptide may be processed to a 13 amino acid peptide, obestatin (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Further information is required to establish exactly how obestatin (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) is formed, although, a recent study indicates that this isoform is indeed biologically active [62].…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of a C-terminal Gly-Lys motif, amidation of obestatin was assumed and verified as a prerequisite for biological activity [162]. Furthermore, the mass spectrometric data indicated that this peptide may be processed to a 13 amino acid peptide, obestatin (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Further information is required to establish exactly how obestatin (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) is formed, although, a recent study indicates that this isoform is indeed biologically active [62].…”
Section: 3mentioning
confidence: 99%
“…Recently, it was demonstrated that ghrelin can inhibit the activity of the glucosensing neurons (glucose-inhibited and glucose-excited neurons) in the dorsal vagal complex of rats [118,152]. Depending upon the experimental condition, ghrelin has been reported to be able to either inhibit or stimulate insulin secretion in animals and humans [14]. Nevertheless, most available data suggest a negative association between systemic ghrelin and insulin levels, with ghrelin inhibiting insulin secretion both in vitro and in most human or animal studies [14].…”
Section: Glucose Metabolismmentioning
confidence: 99%
“…Ghrelin may have direct biological action within the pancreas, potentially functioning during pancreatic development. Although these results remain controversial, in vivo peripheral administration of ghrelin modulated plasma insulin and glucose levels [4][5][6][7]. The growth hormone secretagogue receptor (GHS-R), for which ghrelin can serve as a ligand, is expressed in the pancreas [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Ghrelin was also shown to mediate diabetic hyperphagia 42 and to regulate glucose homeostasis by direct action in the pancreas, being able to supress insulin secretion in vitro and increase glucose in vivo, 43,44 while insulin reduces ghrelin levels suggesting the existence of an inverse relationship between the two hormones. 45 In addition, bariatric surgery has been demonstrated to interfere with appetite regulating pathways, inducing changes in gastro-intestinal hormones levels that could contribute to weight loss, in particular by suppressing the rise in ghrelin levels that is normally observed after caloric deprivation.…”
Section: Ghrelinmentioning
confidence: 99%